The Effectiveness of a Cognitive-Behavioral Program to Improve Self-Affirmation among Orphan Students in the Gaza Stripهدفت الدراسة إلى بيان فعالية برنامج معرفي سلوكي لتحسين توكيد الذات لدى الأيتام في قطاع غزة، واستخدم الباحثان المنهج شبه التجريبي، وتكونت (Journal Of Educational and Psychological Researches, 2024)
The research aims to demonstrate the effectiveness of a cognitive-behavioral program to improve self-affirmation among orphans in the Gaza Strip. The researchers used a semi-experimental approach. The study sample consisted of 30 children from orphanages. The study sample was divided into two groups: the control group of 15 children and the experimental group of 15  children. A self-affirmation questionnaire developed by the two researchers was used. Also, the researchers prepared a cognitive-behavioral program to improve self-affirmation. The results showed that there is a statistically significant difference between the experimental and control groups in favor of the experimental group. There are statistically significant differences in the pre-and post-application on the self-affirmation questionnaire in favor of the experimental group, and the differences were in favor of the post-application on the questionnaire. The study recommends circulating the program to specialists who work with orphans in order to raise their level of self-assertion. The Al-Amal Institute for Orphans also recommended implementing educational meetings and workshops aimed at self-assertion among orphans in scientific ways. The study also recommended the need to follow up on children and provide appropriate programs that help them develop their personalities and self-confidence, as well as the necessity of creating programs that improve their personal and social characteristics.